Finite Time Blow Up of Solution for 1-D Nonlinear Wave Equation of Sixth Order with Linear Restoring Force at High Energy Level (Journal of Partial Differential Equations, 2018)
This paper is concerned with the Cauchy problem for some 1-D nonlinearwave equations of sixth order with linear restoring force. By utilizing the concavitymethod and the technique of anti-dissipativity a finite time blow up result of certainsolutions with arbitrarily positive initial energy is presented.
Keywords: Cauchy problem; wave equation; sixth order; blow up; arbitrarily positive initial energy.